Textile Wastewater Post Treatment Using Ozonation - Noviani Ima Wantoputri; Qomarudin Helmy; Suprihanto Notodarmojo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The textile industry is one of the industries that discharge an enormous quantity of highly colored wastewater because of the large amount of water used in the process. Textile wastewater is the potential to polluting the environment due to the high color contained in it. One of the problems in processing textile wastewater with conventional treatment methods is the ineffectiveness of color removal. A post-treatment is needed for treated wastewater to remove the color. One of the methods is by using the ozonation method. In this preliminary study, the decolorization of artificial textile wastewater containing azo dye reactive-black 5 (RB5) from secondary treatment was investigated in a batch system. Artificial treated textile wastewater from secondary biological treatment was made using 5,26 mg/L azo dye RB5 in 16 L volume of the reactor. The preliminary batch study showed that the optimum color removal achieved in 24.66 mg/minute ozone dose in a batch system with 20,89 mg/minute ozone consumption. Within 5 minutes of ozonation, color removal achieved was 100%, and COD removal achieved was 75%.